Kampanye Semarang Wegah Nyampah dan Engagement Publik - Widiyasari, Eka; Prathama, Nikolaus Ageng; Nugroho, Adi (SOURCE : Jurnal Ilmu Komunikasi, 2024)
This research discusses the "Semarang Wegah Nyampah" campaign conducted by the Communication Division of the Regional Secretariat of Semarang City. The campaign aims to promote an environmentally friendly lifestyle and public awareness of the impact of waste, especially single-use plastic waste. However, the campaign has not been effective due to its limited reach and lack of high interaction on Instagram and TikTok social media platforms. The purpose of this research is to describe the process of forming public engagement in the Semarang Wegah Nyampah campaign, using concepts such as Persuasive Communication, Types of Campaigns, Public Policy, Social Psychology, and the Pyramid Model of PR Research. The research methodology employed is qualitative-descriptive, involving direct observation, in-depth interviews, and document analysis. The findings of this research indicate that the Semarang Wegah Nyampah campaign has had a positive impact on waste management in Semarang City. Despite facing challenges, the campaign has successfully increased awareness and changed behaviors related to waste management. However, the campaign's message has not been effectively disseminated, and public participation needs improvement. To achieve larger goals and create a greater impact on the public, further efforts are required to widely disseminate the campaign's message, enhance public knowledge, and integrate public policies. Therefore, the Semarang Wegah Nyampah campaign can continue to play a significant role in creating a clean and sustainable environment in Semarang City.